2007
DOI: 10.1002/14651858.cd000123.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-lowering for peripheral arterial disease of the lower limb

Abstract: Analysis 1.1. Comparison 1 Any lipid-lowering regimen vs control: all trials, Outcome 1 All-cause mortality.. .. Analysis 1.2. Comparison 1 Any lipid-lowering regimen vs control: all trials, Outcome 2 Total cardiovascular events. Analysis 1.3. Comparison 1 Any lipid-lowering regimen vs control: all trials, Outcome 3 Fatal cardiovascular.. .. Analysis 1.4. Comparison 1 Any lipid-lowering regimen vs control: all trials, Outcome 4 Non-fatal cardiovascular events. Analysis 1.5. Comparison 1 Any lipid-lowering regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 77 publications
2
98
0
15
Order By: Relevance
“…As for cardiac events, a systematic review of 18 trials including .10 000 patients, with cholesterol levels ranging from normal to elevated, reported that lipid-lowering therapy in subjects affected by atherosclerosis of the lower limbs is associated with a 20% reduction in total CV events, together with a non-significant 14% reduction of all-cause mortality. 407 Regarding limb prognosis, in the Reduction of Atherothrombosis for Continued Health (REACH) registry, statin use was associated with an 18% lower rate of adverse limb outcomes. 408 Even in the most advanced stages of the disease (critical limb ischaemia), statin therapy improved rates of 1-year mortality and major adverse CV events and increased amputation-free survival.…”
Section: Peripheral Arterial Diseasementioning
confidence: 99%
“…As for cardiac events, a systematic review of 18 trials including .10 000 patients, with cholesterol levels ranging from normal to elevated, reported that lipid-lowering therapy in subjects affected by atherosclerosis of the lower limbs is associated with a 20% reduction in total CV events, together with a non-significant 14% reduction of all-cause mortality. 407 Regarding limb prognosis, in the Reduction of Atherothrombosis for Continued Health (REACH) registry, statin use was associated with an 18% lower rate of adverse limb outcomes. 408 Even in the most advanced stages of the disease (critical limb ischaemia), statin therapy improved rates of 1-year mortality and major adverse CV events and increased amputation-free survival.…”
Section: Peripheral Arterial Diseasementioning
confidence: 99%
“…[14] у данной категории больных целевой уровень ХС-ЛПНП составляет <1,5 ммоль/л или уменьшение его более чем на 50%, либо снижение, по меньшей мере, на 50%, если исходный уровень ХС-ЛПНП составлял 1,5-3,5 ммоль/л. У пациентов с ЗАНК терапия статинами улучшает как сердечно-сосудистые исходы, так и исходы по со-бытиям, связанным с конечностями [30]. В наблюда-тельных (обсервационных) исследованиях и в ограни-ченном количестве РКИ у пациентов с ЗАНК (как с асимптомным течением ЗАНК, так и с критической ишемией конечности) терапия статинами снижала об-щую смертность и частоту сердечно-сосудистых событий [30][31][32].…”
Section: Fixed Combination Of Rosuvastatin and Acetylsalicylic Acid фunclassified
“…У пациентов с ЗАНК терапия статинами улучшает как сердечно-сосудистые исходы, так и исходы по со-бытиям, связанным с конечностями [30]. В наблюда-тельных (обсервационных) исследованиях и в ограни-ченном количестве РКИ у пациентов с ЗАНК (как с асимптомным течением ЗАНК, так и с критической ишемией конечности) терапия статинами снижала об-щую смертность и частоту сердечно-сосудистых событий [30][31][32]. Так, в подгруппе из 6748 пациентов с ЗАНК в HPS (Heart Protection Study) применение 40 мг симва-статина ежедневно снижало риск первого серьезного сосудистого события на 22% по сравнению с плацебо [31].…”
Section: Fixed Combination Of Rosuvastatin and Acetylsalicylic Acid фunclassified
“…Окклюзирующий атеросклероз артерий нижних конеч-ностей и экстракраниальных артерий рассматриваются как эквиваленты ИБС, поэтому ХС-снижающая терапия таким пациентам должна назначаться независимо от уровня липидов в плазме крови [472,486] . Однако, увеличение ТКИМ каротидных артерий без признаков атеросклероти-ческих бляшек не является показанием для назначения ХС-снижающей терапии у пациентов без подтвержденного ССЗ или других факторов риска .…”
Section: пациенты с заболеваниями периферических артерийunclassified